Quantum-confined bandgap narrowing of TiO2 nanoparticles by graphene quantum dots for visible-light-driven applications. Issue 59 (14th June 2016) - Wang, Shujun; Cole, Ivan S.; Li, Qin
Abstract : We for the first time report a quantum-confined bandgap narrowing mechanism through which the absorption of two UV absorbers, namely the graphene quantum dots (GQDs) and TiO2 nanoparticles, can be easily extended into the visible light range in a controllable manner. Abstract : We for the first time report a quantum-confined bandgap narrowing mechanism through which the absorption of two UV absorbers, namely the graphene quantum dots (GQDs) and TiO2 nanoparticles, can be easily extended into the visible light range in a controllable manner. Such a mechanism may be of great importance for light harvesting, photocatalysis and optoelectronics.